ANALISIS RISIKO TERHADAP PERILAKU YANG MEMBAHAYAKAN PADA PENGEMUDI DUMP TRUCK DALAM PENGANGKUTAN BATUBARA DI PT BAHANA BUMI MANDIRI KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Aprilliana , Aprilliana; Thoriq Haviz Zurafi; Muchtar Arifin (Bajang Institute, 2025)
PT Bahana Bumi Mandiri is an experienced logistics and contractor transportation provider company since 2016 located in South Sumatera. One of the accident prevention programs at PT Bahana Bumi Mandiri’s operations is to emphasize the importance of communication with dump truck drivers, and one form of implementing this programis to ensure that the unit is on the dump truck driver when operating. The aim of this research is to find out the risk of dangerous behavior of dump truck drivers when transporting coal and to find out efforts to improve or solve the risk and behavior that have been caused by dump truck drivers when transporting coal. The standard used at PT Bahana Bumi Mandiri is P2H (Daily Inspection and Checking). The implementation of safe driving at PT Bahana Bumi Mandiri is still relatively minimal so it is necessary to add safety driving to reduce potential dangers that could occur. However, it is necessary to know first the attitude of dump truck drivers by asking question in the form of a questionnaire so the data is processed so that the results can be known. If the need for safe driving in mines is not implemented more fully, it can increase the risk of accidents or incidents in the work emvironment.